Quantized Feedback Control of Network Empowerment Ammunition with Data-Rate Limitations - Fang Jin; Zhi-hua Yuan; Qing-Quan Liu; Zhang Xing (Universitas Ahmad Dahlan, 2014)
This paper investigates quantized feedback control problems for network empowerment ammunition, where the sensors and the controller are connected by a digital communication network with data-rate limitations. Different from the existing ones, a new bit-allocation algorithm on the basis of the singular values of the plant matrix is proposed to encode the plant states. A lower bound on the data rate is presented to ensure stabilization of the unstable plant. It is shown in our results that, the algorithm can be employed for the more general case. An illustrative example is given to demonstrate the effectiveness of the proposed algorithm.